Analysis of Understanding Concepts and Obstacles to Understanding Concepts of Thermodynamics in Physics Lessons - Pandiangan, Jelita Anggriani (Al-Khazini, 2024)
This study aims to analyze the concept understanding and concept understanding constraints of students of class XI IPA 1 SMA Negeri 1 Dolok Batu Nanggar on thermodynamic material in physics lessons. The research method used in this research is a quantitative descriptive method with a research sample of 30 students of class XI IPA 1 SMA Negeri 1 Dolok Batu Nanggar. The instrument used is a questionnaire containing questions about thermodynamic concepts.The results showed (1) The understanding of the concept of students in class XI IPA 1 at SMA Negeri 1 Dolok Batu Nanggar is categorized as moderate in terms of understanding the concept of Thermodynamics material in physics lessons with a percentage of 50%. (2) The highest obstacle experienced by students of class XI IPA 1 at SMA Negeri 1 Dolok Batu Nanggar in understanding the concept of thermodynamic material in physics lessons is the lack of supporting resources such as textbooks or additional learning materials which makes thermodynamics difficult to understand by students with a percentage of 80%. (3) The concept of thermodynamics that is most difficult to understand by students of class XI IPA 1 at SMA Negeri 1 Dolok Batu Nanggar in thermodynamics material is that students find it difficult to understand the carnot cycle series shown in a graph with a percentage result of 63.3%.